Variations of physical properties, bioactive phytochemicals, antioxidant capacities and PPO activities of cantaloupe melon (Cucumis melo L.) slices subjected to different drying methods - Gao, Xin; Yang, Junyan; Wang, Haojie; Mao, Jiancai; Wu, Lipeng; Li, Junhua; Wang, Xuhui (Frontiers in Nutrition, 2025)
In order to prolong the market life and maintain the health benefits of cantaloupe melon (Cucumis melo L.), the present study compared the influences of three commonly used methods in drying cantaloupe melon slices. Drying methods applied included microwave drying (MD), freeze drying (FD), and hot air drying at 40°C (HD40), 50°C (HD50), 60°C (HD60), and 70°C (HD70). Physical changes such as moisture, color, volume shrinkage ratio, hardness, and rehydration ratio under different drying methods were firstly evaluated. Besides, content of free amino acids, soluble sugar, total phenolics, flavonoids, and some individual bioactive compounds such as ascorbic acid, β-carotene, rutin, gallic acid, chlorogenic acid, and caffeic acid were measured. In addition, in vitro antioxidant activities evaluated by DPPH, FRAP and ABTS methods and polyphenol oxidase activities were also determined. On the whole, FD was the best method in maintaining physical changes, content of phytochemicals and antioxidant activities. MD was better than HD in drying cantaloupe melon slices. Of the HD treatments, HD60 was better than others. The findings of the present study can provide the scientific basis for future large-scale production of dried cantaloupe melon slices.